Calculation and 3D analyses of ERR in the band crack front contained in a rectangular plate made of multilayered material - Dincel, Arzu Turan; Akbarov, Surkay D. (DE GRUYTER POLAND SP ZOO, 2018)
An investigation into the values of the Energy Release Rate (ERR) at the band crack's front in the rectangular plate made of multilayered composite material is carried out for the opening mode. The corresponding boundary-value problem is modelled by using three-dimensional linear theory and solved numerically by using 3D FEM (Three Dimensional Finite Element Method). The main purpose of the current investigation is to study the influence of mechanical and geometrical parameters on the Energy Release Rate (ERR) at this crack front. The numerical results related to the ERR, and the effect of the mechanical and other problem parameters on the ERR are presented and discussed.
Keywords: Energy Release Rate (ERR); band crack; 3D FEM (Three Dimensional Finite Element Method); rectangular plate; ENERGY-RELEASE RATE; BRITTLE INTERFACIAL CRACKING; STRIP; LAYERS; TIPS; GROWTH; Chemistry